Exploring Linguistic and Cultural Diversity: An Analysis of Multi-lingual and Multi-cultural Representation in Jazz-Warid Television Commercials in Pakistan - Fatima Toor; Ammara Afzaal; Hafsa Karamat Meo (University of Chitral Journal of Linguistics and Literature, 2024)
In the realm of advertising, the utilization of diverse linguistic techniques has become pivotal in captivating audiences across varying cultural and linguistic landscapes. This paper delves into the nuanced strategies employed by advertisers, specifically focusing on the incorporation of code-mixing and code-switching in advertisements to resonate with diverse demographic segments. Employing a qualitative research methodology, this study aims to elucidate the intricate mechanisms through which advertisers leverage linguistic diversity to garner attention and engagement from heterogeneous audiences. Through a meticulous analysis of advertisements, this research uncovers the multifaceted nature of language manipulation in advertising campaigns. By intertwining elements of different languages and cultural representations, advertisers effectively navigate the linguistic tapestry of a multicultural society, thereby enhancing the relatability and appeal of their messaging to broader consumer bases. Furthermore, this study sheds light on the inherent power of language in shaping consumer perceptions and behaviors, emphasizing its role as a potent tool for audience engagement and brand communication. The findings of this study underscore the significance of linguistic diversity as a strategic asset in contemporary advertising practices. By harnessing the synergistic potential of code-mixing and code-switching techniques, advertisers can transcend linguistic barriers and forge meaningful connections with diverse audiences. Ultimately, this research contributes to a deeper understanding of the symbiotic relationship between language, culture, and consumer behavior, highlighting the pivotal role of language in shaping advertising effectiveness and consumer engagement on a mass scale.